P17.07 Sexual risk behaviour predicts more frequent use of hiv self-testing: early findings from the forth trial. (13th September 2015) - Guy, R; Jamil, MS; Fairley, C; Smith, K; Grulich, A; Bradley, J; Kaldor, J; Chen, M; McNulty, A; Holt, M; Ryan, D; Batrouney, C; et al.
Abstract : Background: Most HIV diagnoses in Australia are among gay and bisexual men (GBM), yet less than a quarter of higher-risk GBM are testing at the recommended frequency (3–6 monthly). In the context of a randomised trial of HIV self-testing (FORTH), we examined the predictors of more frequent use of HIV self-testing among higher-risk GBM. Methods: Participants in FORTH trial included higher-risk GBM (>5 sexual partners or condomless anal intercourse in the past 3 months). The trial is being conducted over 12 months, and men in the intervention arm receive 4 self-tests (OraSure's OraQuick home test) at baseline and additional self-tests on request. Using data from the baseline and 6 month surveys, we used logistic regression to examine predictors of using >2 self-tests over 6 months among participants in the intervention arm. Results: Of the GBM (n = 154) in the intervention arm, 59% reported in the baseline survey they had condomless anal intercourse with casual partners (CLAIC) in the past 6 months and 56% had a HIV test every six months. Men who reported CLAIC in the past 6 months were more likely to use >2 HIV self-tests in the first 6 months of the trial (odds ratio:2.8, 95% CI: 1.2–6.7). No other baseline survey factors were associated with >2 self-tests, including; demographics, testing frequency, likelihood to self-test in the future, and reported testing barriers (the process of getting tested is too much hassle, I don't like having to return for results, I don't want to go to a clinic/doctor to get tested). Conclusion: These findings indicate men who report sexual risk behaviour are more likely to increase their testing frequency through self-tests, which is a key HIV prevention goal. However there is also a need to ensure the longer window period of the OraQuick self-test is understood to avoid infections being missed. Disclosure of interest statement: The research is funded through a NHMRC Program grant from the NHMRC and self-test kits were purchased from OraSure Technologies Inc. (Bethlehem, PA, USA). The Kirby Institute and the Centre for Social Research in Health receive funding from the Australian Government Department of Health.